Using Different Feed Additives as Alternative to Antibiotic Growth Promoter to Improve Growth Performance and Carcass Traits of Broilers - Hassan, H.M.A.; Samy, A.; Youssef, Amani W.; Mohamed , M.A. (International Journal of Poultry Science, 2018)
Background and Objective: Several feed additives have been used to improve feed efficiency and growth performance of broiler. This growth experiment aimed to study the effect of using different feed additives compared to Bacitracin Methylene Disalicylate antibiotic growth promoter on growth performance and carcass traits. Methodology: Three hundred broiler chicks were divided into six treatment groups (5 replicates, 10 birds each treatment). A basal corn-soybean meal diet was formulated. Treatment 1 was basal diet without additives (as a control group); treatments 2, 3, 4, 5 and 6 were the control diet supplemented with 0.025% Bacitracin Methylene Disalicylate (antibiotic), 0.05% Saltose (probiotic), 0.05% Clostat (probiotic), 0.05% Clostri-stop (probiotic) or 0.1% Sangrovit (phytobiotic), respectively. Results: The results showed that supplementation of different feed additives or antibiotic significantly (p